2002
DOI: 10.1016/s0899-9007(02)00939-5
|View full text |Cite
|
Sign up to set email alerts
|

Planning strategies for development of effective exercise and nutrition countermeasures for long-duration space flight

Abstract: Exercise and nutrition represent primary countermeasures used during space flight to maintain or restore maximal aerobic capacity, musculoskeletal structure, and orthostatic function. However, no single exercise, dietary regimen, or combination of prescriptions has proven entirely effective in maintaining or restoring cardiovascular and musculoskeletal functions to preflight levels after prolonged space flight. As human space flight exposures increase in duration, identification, assessment, and development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…In this context, it appears particularly important to define the impact of countermeasures at the cellular and molecular levels. Skylab space missions were the first to include a countermeasure program involving astronaut exercises ranging from 30 to 90 min/day with a clear emphasis on aerobic metabolism (25). Both space and ground experiments have already demonstrated that maximal resistance exercise is effective in preserving muscle structure and function (3,79,80) and that nutritional aid is key in the maintenance of the muscle mass, well-being and performance of the astronauts (70,72).…”
mentioning
confidence: 99%
“…In this context, it appears particularly important to define the impact of countermeasures at the cellular and molecular levels. Skylab space missions were the first to include a countermeasure program involving astronaut exercises ranging from 30 to 90 min/day with a clear emphasis on aerobic metabolism (25). Both space and ground experiments have already demonstrated that maximal resistance exercise is effective in preserving muscle structure and function (3,79,80) and that nutritional aid is key in the maintenance of the muscle mass, well-being and performance of the astronauts (70,72).…”
mentioning
confidence: 99%
“…However, these devices are uncomfortable or lack sufficient loads to maintain preflight musculoskeletal mass. The optimal protocol and equipment for exercise in space are still unresolved (5). Over the past 10 yr, we have developed a lower body negative pressure (LBNP) treadmill exercise system that provides both cardiovascular and musculoskeletal responses equivalent to upright exercise in gravity (3,9,21,31).…”
mentioning
confidence: 99%
“…A single bout of maximal exercise increased the responsiveness of the arterial baroreflexes after acute exposure to microgravity. Therefore the development of effective exercise and nutrition countermeasures designed to maintain baroreflex functions could prove instrumental in ameliorating the deleterious effects of microgravity on cardio-vascular mechanisms [30]. Although the baroreflexes and the vestibulosympathetic reflex do not appear to interact centrally to modify sympathetic outflow during an orthostatic challenge, they complement each other [31,32].…”
Section: Discussionmentioning
confidence: 99%